Improvement of asphalt mixture by adding components of tires waste (rubber - steel fibers) (Journal of Hama University, 2024)
In this research, the effect of each of the rubber granules and steel fibers extracted from tire waste on the properties of asphalt mixture was studied, where the bitumen was modified with rubber granules, and then the steel fibers were added to the modified asphalt mix. : 3 - 7 - 10 - 15% by weight of bitumen, steel fibers: 0.5 - 1 - 2% by weight of asphalt mixtures) It was noted that the Marshall stability values improved, which increased by 126% when adding 15% rubber granules and 1% steel fibers. Indirect tensile test, the percentage of increase in resistance in the same sample reached 123%. The relationship of the American Asphalt Institute was employed to predict the dynamic resilience coefficient of the asphalt mixture layer, and the (3D Move Analysis) program was used to study the effect of repeated loads on the response of the pavement designed with an asphalt mixture layer with elastic-viscous behavior and a rate of previous additions, according to the criteria of fatigue and rutting, where Loading is dynamic and the coefficient of elasticity is variable according to the temperature of the surface layer of the pavement. The study showed an increase in the number of repeated loads until reaching collapse from /838384/ load cycle to /2460001/ load cycle at the previous ratio. Finally, several results and recommendations were reached.
Keywords: tires waste; rubber; asphalt mixture; dynamic modulus of elasticity; asphalt institute; steel fibers